The CardioVASS Heart Model: Comparison of Biomaterials between TPU Flex and Soft Epoxy Resin for Biomedical Engineering Application - Nur Afikah, Khairi Rosli; Mohd Azrul Hisham, Mohd Adib; Nurul Natasha, Mohd Sukri; Idris, Mat Sahat; Nur Hazreen, Mohd Hasni (IEEE, 2021)
Nowadays, the implementation of the polymer biomaterial for the fabrication of the heart model is still considered new. To improve the materials used in the fabrication, many researchers tried to merge and constructed new biomaterials that represent the good quality of a heart model, in line with the industrial revolution (IR 4.0). However, it is hard to gain cost-efficient raw materials, and the material supply also difficult to obtain. This paper represents a continuous study regarding the CardioVASS device with the development of the materials used for the heart model. The objective of this paper is to study the comparison of the TPU and soft epoxy resin material on the development of the CardioVASS heart model. The microstructure analysis and the tensile testing had been conducted for a better understanding of the material mechanical properties respectively. The curve stress-strain and the load-displacement graphs were obtained from the experiment. The results show that the TPU flex material has a higher strength compared to the soft epoxy resin. The microstructure analysis founded that the TPU flex was elastic than the epoxy resin. Both of the material was able to be developed as the heart model. In conclusion, the TPU flex material has better mechanical properties to be fabricated as a heart model compared to the epoxy resin material.